ความพึงพอใจของลูกค้าต่อส่วนประสมการตลาดของห้างหุ้นส่วนจำกัด วินเตอร์เทค - สุธาทิพย์ สุขสราญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to study customer satisfaction towards marketing mix of Wintertech Limited Partnership. The population was specified to 278 respondents of the Wintertech Limited Partnership; but only 257 of them returned the questionnaires, as the tool to to collect data. The data was then analyzed using frequency, percentage and mean, as well as the T-test for paired samples. The results presented that most respondents were male in age of 31-40 years old, married/domestic partnership, with Bachelor’s degree and were in the position of Assistant/Manager of Procurement Division. Their business was operated as company limited with registered capital at 1 – 10 million baht. The operating period of their business was 6-10 years of operating period and its annual turnover was 15,000,001-20,000,000 baht. A criterion for purchasing decision making of printing materials depended on user’s requirement and their selected method of purchase was to purchase products from several suppliers. The period of purchasing products from Wintertech Limited Partnership was 2-5 years, with the purchasing frequency at once in 1-3 months. Product that they purchased at most was the plate cleaner. They learned about product information mostly from salespersons. The respondents had high level of expectations towards marketing mix of Wintertech Limited Partnership in an overview. Top expectation at the means = 4.37 was found in promotion factor; followed by product factor at the means = 4.34, price factor at the means = 4.32, and place factor at the means = 4.21, respectively. The respondents had high level of perceptions towards marketing mix of Wintertech Limited Partnership in an overview at the means = 3.75. Top perception at the means = 3.84 was found in product factor; followed by promotion factor at the means = 3.79, place factor at the means = 3.69, and price factor at the means = 3.67, respectively.